2015
DOI: 10.1007/s12185-015-1743-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study in Japan of siltuximab, an anti-IL-6 monoclonal antibody, in relapsed/refractory multiple myeloma

Abstract: Siltuximab, a chimeric monoclonal antibody with high affinity and specificity for interleukin-6, has been shown to enhance anti-multiple myeloma activity of bortezomib and corticosteroid in vitro. We evaluated the safety, pharmacokinetics, immunogenicity, and antitumor effect of siltuximab in combination with bortezomib and dexamethasone in Japanese patients with relapsed or refractory multiple myeloma. This open-label, phase 1, dose-escalating study used two doses of siltuximab: 5.5 and 11.0 mg/kg (administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Taken together, on the basis of these findings, IL‐6 can be considered as a therapeutic target in cancer. At present, some antibodies against IL‐6 or IL‐6R are under evaluation in phase I/II clinical trials including siltuximab (CNTO 328), a monoclonal antibody against IL‐6, has shown promising results for non‐small cell lung cancer (NSCLC), ovarian cancer, prostate cancer, and multiple myeloma …”
Section: Mechanisms Of Obesity‐related Cancermentioning
confidence: 99%
“…Taken together, on the basis of these findings, IL‐6 can be considered as a therapeutic target in cancer. At present, some antibodies against IL‐6 or IL‐6R are under evaluation in phase I/II clinical trials including siltuximab (CNTO 328), a monoclonal antibody against IL‐6, has shown promising results for non‐small cell lung cancer (NSCLC), ovarian cancer, prostate cancer, and multiple myeloma …”
Section: Mechanisms Of Obesity‐related Cancermentioning
confidence: 99%
“…Despite promising preclinical results and the strong molecular rationale for targeting IL-6 and the IL-6 receptor in combination with Btz, clinical trials conducted to date have not demonstrated overwhelming benefit for combining the two agents. A recent phase I study of single agent siltuximab, an IL-6-targeted monoclonal antibody (MAb), in Japan showed good tolerability and activity in refractory MM patients (Suzuki et al, 2015), although a phase II, double-blind, placebo-controlled trial of siltuximab in combination with Btz showed no significant improvement in progressionfree survival (PFS) or OS compared to siltuximab plus placebo (Orlowski et al, 2015). Similar results were observed when siltuximab was added to a multidrug regimen that included Btz.…”
Section: Il-6/stat3 Signaling Axismentioning
confidence: 95%
“… 17 Based on the above results, siltuximab addition was considered for melphalan-based or bortezomib-based therapies. 27 However, in another study, the addition of siltuximab to the bortezomib–melphalan–prednisone regimen does not seem to improve complete response, progression-free survival, and overall survival, it only improves very good partial responses in patients who are transplant ineligible with newly diagnosed MM. 4 …”
Section: Clinical Studiesmentioning
confidence: 98%
“…Across both doses, 66% patients had complete or partial response, and 11.0 mg/kg once every 3 weeks is recommended. 27 In the Phase II randomized controlled clinical trial, the safety and efficacy of siltuximab plus bortezomib with placebo in patients with relapsed/refractory MM were assessed. Siltuximab was given by 6 mg/kg intravenous every 2 weeks, and after the study, it was found that the addition of siltuximab to bortezomib did not improve progression-free survival or overall survival despite a numerical increase in response rate in patients with relapsed or refractory MM.…”
Section: Clinical Studiesmentioning
confidence: 99%